Pengembangan Metode Griess dengan Reduktor Logam Seng Berlapis Tembaga untuk Penetapan Kadar Metabolit Oksida Nitrat dalam Serum - Armita Sari, Pande Made Nova; Warditiani, Ni Kadek; Astuti, Ni Made Widi; Wirasuta, I Made Agus Gelgel (Jurnal Farmasi Udayana, 2021)
The recent research concerned in method development for determination of nitric oxide metabolites in serum using spectrophotometry visible based on Griess reaction. The reduction of nitrate to nitrite was performed using copper coated zinc. The method was optimized and validated. The determination of total nitrite in samples  was started with deproteinization using ZnSO4 and NaOH. The supernatants were reducted using copper coated zinc, reacted with diazotization and coupling reagents, then incubated. The absorbance was measured using spectrophotometer visible. The optimum reductant mass of copper coated zinc is 1.5 g with reduction time 10 minutes, coefficient variation ? 5%. Linierity of analytical method gives a coefficient correlation, r > 0.995. Relative procedural standard deviation (Vx0) was ? 5%, precision ? 15%, and recovery 85-115%.